2020
DOI: 10.1155/2020/3619063
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Study of Tuberculosis Incidence by ARMA Model Combined with Air Pollution Variables

Abstract: China has the second largest number of tuberculosis (TB) cases in the world, and the Xinjiang province has the highest TB incidence in China. Urumqi is the capital city of Xinjiang; good TB prevention and control in Urumqi can provide an example for other parts of Xinjiang, considering that predicting the TB incidence is the prerequisite of prevention and control; therefore, it is necessary to do a prediction study on TB incidence in Urumqi. In this paper, based on the data of TB incidence and air pollution va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Experiments prove that the adaptive ARMA model is more accurate than the traditional ARMA model in forecasting 24 hours and one week in advance. Yanling Zheng et al [9] based on the data of tuberculosis incidence and air pollution variables (PM2.5, PM10, SO2, CO, NO2, O-3) in Urumqi, the ARMA (1, (1, 3)) + model was established by time series ARMA model method, cross-correlation analysis, and principal component regression method, and its predictive performance was superior to that of the ARMA (1, (1, 3)) model based on tuberculosis historical data. During the analysis, it was found that the higher the concentration of O-3, the higher the incidence of tuberculosis .…”
Section: )The Classic Linear Models (1) Prediction Model For Stationary Datamentioning
confidence: 99%
“…Experiments prove that the adaptive ARMA model is more accurate than the traditional ARMA model in forecasting 24 hours and one week in advance. Yanling Zheng et al [9] based on the data of tuberculosis incidence and air pollution variables (PM2.5, PM10, SO2, CO, NO2, O-3) in Urumqi, the ARMA (1, (1, 3)) + model was established by time series ARMA model method, cross-correlation analysis, and principal component regression method, and its predictive performance was superior to that of the ARMA (1, (1, 3)) model based on tuberculosis historical data. During the analysis, it was found that the higher the concentration of O-3, the higher the incidence of tuberculosis .…”
Section: )The Classic Linear Models (1) Prediction Model For Stationary Datamentioning
confidence: 99%
“…Several studies have shown the effect of air pollution on the PTB cases in Urumqi. For example, an ARMA (1, (1, 3)) + model was established to analyze the correlation between air pollutants and the incidence of PTB in Urumqi from 2014 to 2017 and found that the higher concentration of O 3 , the higher PTB incidence [ 13 ]. Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the effect of air pollution on the PTB cases in Urumqi. For example, an ARMA (1, (1, 3)) + model was established to analyze the correlation between air pollutants and the incidence of PTB in Urumqi from 2014 to 2017 and found that the higher concentration of O 3 , the higher PTB incidence [13]. Yang et al [14] used a generalized additive model to analyze the relationship between air pollutants and PTB incidence and it was indicated that the combined effect of PM 10 and NO 2 had the greatest impact on the incidence of tuberculosis.…”
Section: Introductionmentioning
confidence: 99%